Pola konsumsi makanan keluarga miskin perkotaan dalam pusaran kapitalisme nutrisi - Andi Alim; Arlin Adam; Ashriady Ashriady (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Low-income families' understanding of nutrition is still irrational because they still use myths about consumption that cause malnutrition in their children. It is exacerbated by the influence of advertising so that the behavior of family consumption patterns is systematically constructed. The research explores the transformation of consumer behavior that causes malnutrition and the role of nutrition capitalism in meeting nutritional needs. A qualitative study design using a critical paradigm was conducted in Makassar City in 2021. Research informants are urban low-income families. Data were collected using interviews and Focus Group Discussions and analyzed qualitatively. The result is that malnutrition in low-income families is caused by people's knowledge and tastes constructed by industrial power and leads people to consume industrial food. The transformation of consumption behavior of low-income families is caused by the operation of nutritional capitalism, which is present in various forms such as industrial processed food advertisements and franchise outlets. In conclusion, the consumption behavior of the poor is constructed by food and beverage capitalism. In addition, the advertising factor has an impact on nutritional capitalism.